Study guides

☆☆

Q: X2 plus 4x - 9 equals 5x plus 3?

Write your answer...

Submit

Still have questions?

Related questions

x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4

2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2

-x2+2x

y = 4x-3

4x2 -x -1 :D

x3-x2+5x-1 with remainder 7, which the final answer would be written as:x3-x2+5x-1+[7/(4x+3)]

No.

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

x2+4x+4 = 25 x2+4x+4-25 = 0 x2+4x-21 = 0 (x+7)(x-3) = 0 x = -7 or x = 3

x^2+4x+7

2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0

x2-5x+4 = (x-1)(x-4) when factord

People also asked